2011
DOI: 10.1002/ejoc.201101402
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic “Difficult” Michael Reaction of Ketones with Nitrodienes Utilizing a Primary Amine–Thiourea Based on Di‐tert‐butyl Aspartate

Abstract: The primary amine–thiourea based on di‐tert‐butyl (S)‐aspartate and (1R,2R)‐1,2‐diphenylethylene‐1,2‐diamine has been successfully employed in the “difficult” Michael reaction between aromatic ketones or acetone with nitrodienes. The high stability and reactivity of the catalyst led to improved reaction conditions. Thus, the desired products were obtained in high to excellent yields (up to 100 %) and excellent enantioselectivities (up to 99 %) even at elevated temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Asymmetric organocatalyzed Michael addition between α,β- and γ,δ-unsaturated nitro compounds 327 and aldehydes 328 with 5 mol % ( S )-diphenylprolinol silyl ether afforded good to excellent yields of synthetically useful compounds 329 (Scheme ), which can be converted to more complex molecules, such as tetrahydropyran or cyclohexene derivatives. , The influence of the catalyst on stereoselectivity has been investigated by isotopic labeling experiments, which have shown that mechanisms through the enamine and enol may operate simultaneously . In addition, similar processes for the one-pot enantioselective organocatalytic Michael reaction of aromatic ketones , with nitrodienes or carbonyl compounds with nitrodienes/nitroenynes ,, were carried out with various chiral amine thioureas as catalysts.…”
Section: -Nitro-13-dienesmentioning
confidence: 99%
“…Asymmetric organocatalyzed Michael addition between α,β- and γ,δ-unsaturated nitro compounds 327 and aldehydes 328 with 5 mol % ( S )-diphenylprolinol silyl ether afforded good to excellent yields of synthetically useful compounds 329 (Scheme ), which can be converted to more complex molecules, such as tetrahydropyran or cyclohexene derivatives. , The influence of the catalyst on stereoselectivity has been investigated by isotopic labeling experiments, which have shown that mechanisms through the enamine and enol may operate simultaneously . In addition, similar processes for the one-pot enantioselective organocatalytic Michael reaction of aromatic ketones , with nitrodienes or carbonyl compounds with nitrodienes/nitroenynes ,, were carried out with various chiral amine thioureas as catalysts.…”
Section: -Nitro-13-dienesmentioning
confidence: 99%
“…In addition, the same group proved that the same catalyst (R,R,S)-9 is also able to catalyze the nitro-Michael addition of a variety of aryl methyl ketones and acetone, respectively, to diverse substituted nitrodienes. 39 By elevation of the reaction temperature and pressure, the reaction time was reduced in most cases to an acceptable length whereas the enantioselectivity remained at a high level. With a broad range of substituted ketones and nitrodienes, high to quantitative yields and excellent enantioselectivities were achieved (Scheme 23).…”
Section: Svetlana B Tsogoevamentioning
confidence: 99%
“…Schreiner published the N,N -bis[3,5bis(trifluoromethyl) phenyl]thiourea catalyzed ring opening of epoxides with different nucleophiles such as amines, phenols, and thiols in water with poor regioselectivity (1 : 1 to 1 : 4) [347,348]. Bifunctional primary amine-thioureas catalyze usually difficult Michael reactions [349,350]. Bidentate hydrogen bond donors, urea and thiourea, are found to be useful organocatalysts for the activation of carbonyl group.…”
Section: Heterogeneous Organocatalysts For Their Use Undermentioning
confidence: 99%